EDeSSOpt – Energy Demand and Supply Simultaneous Optimization for cost-optimized design: Application to a multi-family building. (15th February 2019) - Ferrara, Maria; Rolfo, Andrea; Prunotto, Federico; Fabrizio, Enrico
Highlights: Assessment of a new methodology framework for the building design optimization. Evaluation of energy efficiency measures for a multi-family building. Optimal solutions integrating measures for building envelope, energy systems and renewables. Assessment of a method to verify the optimization algorithm stability. Abstract: In the context of European efforts to reduce energy consumption and CO2 emissions in the building sector, the second recast of the Energy Performance of Buildings Directive promotes the acceleration of the energy renovation of European building stock. To do this, a cost optimization is necessary to find the best combination of energy efficiency measures which minimize the global cost during the entire life-cycle of the building, as suggested in the first recast of the same Directive. Since a great number of combinations must be analyzed, an automated procedure is necessary to reduce the calculation time. In this work, an iterative input-output process is set, thanks to the coupling of a dynamic energy simulation software (TRNSYS) and a generic optimization software (GenOpt). The cost optimization is applied to a new social housing construction – a multi-family building located in Northern Italy. The methodology that was adopted allows the simultaneous optimization of both the building energy demand (building envelope) and the building energy supply (technical systems and renewable sources). Results are compared with those obtained using a more widespread sequential approach whose purpose is firstly the optimization of one of these two factors, and subsequently the optimization of the other one. This study has demonstrated that an integrated approach allows a larger number of possible combinations of energy efficiency measures to be explored with respect to the sequential approach.